Diseño de un plan de mantenimiento predictivo para los equipos críticos de una compañía petrolera de servicios de perforación (2024)
The main objective of the project is the design of a predictive maintenance plan for one of the critical equipment of the drills of a drilling services company, focused on the selection of the techniques that best adapt to the operation of the equipment and the selection of the necessary instruments to implement them. Initially, all the theoretical information necessary to understand the concepts that will be discussed during the development of the project and understand the current context of the reference company is collected. It begins with a compilation of information about the basic principles of oil drilling, the process carried out to drill a well and the importance of this industry worldwide. The impact that this process has and the effects that it can cause on the environment, communities and the importance of seeking alternatives that mitigate them are also described. Additionally, it describes how a drilling rig is made up, the use and operation of each of the main equipment.